Ambulatory Arterial Stiffness Index Is Higher in Hypertensive Patients with Chronic Kidney Disease - Ronaldo Altenburg Gismondi; Mario Fritsch Neves; Wille Oigman; Rachel Bregman (International Journal of Hypertension)
Ambulatory arterial stiffness index (AASI) is a parameter obtained from ambulatory blood pressure monitoring (ABPM) that correlates with clinical endpoints. The aim of this study was to compare AASI in nondiabetic hypertensive patients with and without chronic kidney disease (CKD). Subjects with systemic arterial hypertension (SAH, n=30) with normal renal function, aged 40 to 75 years, were compared to hypertensive patients with CKD (n=30) presenting estimated glomerular filtration rate (eGFR) <60 mL/min by MDRD formula. ABPM was carried out in all patients. In CKD group, eGFR was 35.3 ± 2.8 ml/min. The mean 24-hour systolic and diastolic blood pressure (BP) was similar in both groups. AASI was significantly higher in CKD group (0.45±0.03 versus 0.37±0.02, P<0.05), positively correlated to age (r=0.38, P<0.01) and pulse pressure (r=0.43, P<0.01) and negatively correlated to nocturnal BP fall (r=-0.28, P=0.03). These findings indicate the presence of stiffer vessels in CKD hypertensive patients.